Continuous Normothermic Ex Vivo Kidney Perfusion Improves Graft Function in Donation After Circulatory Death Pig Kidney Transplantation. Issue 4 (April 2017) - Kaths, J. Moritz; Echeverri, Juan; Chun, Yi Min; Cen, Jun Yu; Goldaracena, Nicolas; Linares, Ivan; Dingwell, Luke S.; Yip, Paul M.; John, Rohan; Bagli, Darius; Mucsi, Istvan; Ghanekar, Anand; et al.
Abstract : Background: Donation after circulatory death (DCD) is current clinical practice to increase the donor pool. Deleterious effects on renal graft function are described for hypothermic preservation. Therefore, current research focuses on investigating alternative preservation techniques, such as normothermic perfusion. Methods: We compared continuous pressure-controlled normothermic ex vivo kidney perfusion (NEVKP) with static cold storage (SCS) in a porcine model of DCD autotransplantation. After 30 minutes of warm ischemia, right kidneys were removed from 30-kg Yorkshire pigs and preserved with 8-hour NEVKP or in 4°C histidine-tryptophan-ketoglutarate solution (SCS), followed by kidney autotransplantation. Results: Throughout NEVKP, electrolytes and pH values were maintained. Intrarenal resistance decreased over the course of perfusion (0 hour, 1.6 ± 0.51 mm per minute vs 7 hours, 0.34 ± 0.05 mm Hg/mL per minute, P = 0.005). Perfusate lactate concentration also decreased (0 hour, 10.5 ± 0.8 vs 7 hours, 1.4 ± 0.3 mmol/L, P < 0.001). Cellular injury markers lactate dehydrogenase and aspartate aminotransferase were persistently low (lactate dehydrogenase < 100 U/L, below analyzer range; aspartate aminotransferase 0 hour, 15.6 ± 9.3 U/L vs 7 hours, 24.8 ± 14.6 U/L, P = 0.298). After autotransplantation, renal grafts preserved with NEVKP demonstrated lower serum creatinine on days 1 to 7 ( P < 0.05) and lower peak values (NEVKP, 5.5 ± 1.7 mg/dL vs SCS, 11.1 ± 2.1 mg/dL, P = 0.002). The creatinine clearance on day 4 was increased in NEVKP-preserved kidneys (NEVKP, 39 ± 6.4 vs SCS, 18 ± 10.6 mL/min; P = 0.012). Serum neutrophil gelatinase-associated lipocalin at day 3 was lower in the NEVKP group (1267 ± 372 vs 2697 ± 1145 ng/mL, P = 0.029). Conclusions: Continuous pressure-controlled NEVKP improves renal function in DCD kidney transplantation. Normothermic ex vivo kidney perfusion might help to decrease posttransplant delayed graft function rates and to increase the donor pool. Abstract : The authors demonstrate the feasibility and safety of a continuous pressure-controlled normothermic ex vivo kidney perfusion technique in a DCD model. It provides a physiologic environment during graft preservation and results in significantly superior outcomes when compared to static cold storage.